1998
DOI: 10.1046/j.1365-2168.1998.00851.x
|View full text |Cite
|
Sign up to set email alerts
|

New model of renal warm ischaemia–reperfusion injury for comparative functional, morphological and pathophysiological studies

Abstract: This new model allowed comparative functional, morphological and pathophysiological studies while minimizing the number of animals required. Overall 45 min of warm ischaemia gave significant, recoverable injury and is recommended for investigating renal reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 11 publications
2
26
0
Order By: Relevance
“…Renal I/R injury was induced as previously described [8]. Briefly, a midline laparotomy incision was made, followed by a right nephrectomy.…”
Section: Methodsmentioning
confidence: 99%
“…Renal I/R injury was induced as previously described [8]. Briefly, a midline laparotomy incision was made, followed by a right nephrectomy.…”
Section: Methodsmentioning
confidence: 99%
“…In 8/31 publications, the endto-end technique was described. 5,14,16,19,20,22,24,25,35 In 16 publications, the authors favored the end-to-side technique, 1,6À9,11,12,15,17,20,26À29,30,34 and in 6 publications, the sleeve technique 13,18,23,31À33 was favored. Because of the dissection of the shorter renal vessels, the end-to-side technique had to be used in cases of right-sided anastomoses.…”
Section: Surgical Techniquesmentioning
confidence: 96%
“…It is generally believed that the ''warm ischemic time'' must be less than 30 min, and a number of investigators attempted to reduce this time in an effort to minimize ischemic damage. 35 Weight et al demonstrated good correlation between increasing duration of warm ischemic time and degree of renal impairment, both functionally and morphologically. 35 On day 2 there was progressive impairment in the glomerular filtration rate (GFR), 4 with increasing duration of warm ischemic time.…”
Section: Outcomementioning
confidence: 97%
See 1 more Smart Citation
“…The renal IRI model was previously described elsewhere [17]. In brief, a midline abdominal incision was made, followed by right nephrectomy.…”
Section: Experimental Protocol and Renal Iri Modelmentioning
confidence: 99%